(untitled) (Research, Society and Development, 2020)
This work is a clipping of the thesis entitled "Evaluation of teaching praxis as a contribution to professional improvement: the challenge of evaluating who always evaluates" Carvalho (2019). The main objective here is to analyze the documents of the teacher performance evaluation of teachers of the public school system, specifically from the initial years of elementary school in a municipality of Ceará. Based on the theoretical discussion about the teaching evaluation in Brazil, this article analyzes the legal documents that support the function and use of this evaluation (Brasil, 2014; 2015; 2018), considering the present teaching profile of Brazil (Fleuri, 2015) and characteristics of state and municipal teaching evaluations (Rodrigues, 2012; Zatti, 2017; Rezende, 2012; Veras, 2016; Nobre, 2014). Moreover, the bibliographic basis of the conceptual fields "performance evaluation and teaching" are endorsed in Tardif and Lessard (2014), Barretto (2013), Libanio, Oliveira and Toschi (2012); and Scriven (1990), Darling-Hammond (1990) Wise and Gendler (1990) and Fernandes (2008). Of this bibliographic and documentary nature, this research aimed to identify aspects in the instruments of evaluation of teaching performance of a municipality of Ceará relations with the theoretical research then highlighted. With this, it is concluded that the experiences of evaluative system teachers need to take as guiding aspects that base the teaching profession, considering teachers as protagonist subjects of their development and the training policies that can improve it.